Myositis and myasthenia during nivolumab administration for advanced lung cancer: a case report and review of the literature. Issue 5 (June 2020) - Veccia, Antonello; Kinspergher, Stefania; Grego, Elisabetta; Peterlana, Dimitri; Berti, Alvise; Tranquillini, Enzo; Caffo, Orazio
Abstract : The immunotherapy significantly improved survival of non-small cell lung cancer patients, but it may cause immune-related adverse events, which are severe in less than 10% of cases. We report the case of one patient who developed myositis and myasthenia during nivolumab treatment for metastatic lung squamous carcinoma. Moreover, we reviewed literature data in order to identify similar cases in cancer patients treated with immune-checkpoints inhibitors. A 65-year-old patient, who had previously received a first-line platinum-based therapy, developed diplopia and ptosis 4 weeks after the start of nivolumab. Although antibodies associated with myositis, myasthenia gravis and paraneoplastic syndromes were absent, immune-related myositis and myasthenia were diagnosed. Corticosteroids, immunoglobulin and pyridostigmine showed poor efficacy and the patient died 7 weeks after the appearance of the first symptoms. Fifteen similar cases were found in the literature. A close collaboration between different specialists is essential to rapidly identify and treat severe immune-related adverse events.